The Politics of Rights Retention - Samuel A. Moore (Publications, 2023)
This article presents a commentary on the recent resurgence of interest in the practice of rights retention in scholarly publishing. Led in part by the evolving European policy landscape, rights retention seeks to ensure immediate access to accepted manuscripts uploaded to repositories. The article identifies a trajectory in the development of rights retention from something that publishers could previously ignore to a practice they are now forced to confront. Despite being couched in the neoliberal logic of market-centric policymaking, I argue that rights retention represents a more combative approach to publisher power by institutions and funders that could yield significant benefits for a more equitable system of open access publishing.